Kegiatan Jam’iyah Shalawat Solusi Pembentukan Akhlakul Karimah Remaja Di Jatirejo Diwek Jombang - Ali Mustofa; Ika Khoirunni'mah (STIT Muhammadiyah Paciran Lamongan, 2020)
Abstract:Congregation of shalawat, the term itself only appeared around the mid 2000s and above. Previously, the public was more familiar with the terms diba'an, float and so on. The terms of prayer and prayer are very familiar to the people of Indonesia, especially Muslims. Formation of adolescent morality akhakul through activities jam'iyah shalawat Ds. Jatirejo Kec. Diwek Kab. Jombang, the efforts that can be made to establish morality are: Through the habituation process. Intercommunication with people who have noble character (noble character) who are in the environment around the residence and through the teaching process (spiritual splash). adolescents behave well as a polite example to older people and can sort out something good and something bad to do. Supporting factors faced by Jatirejo village adolescents in the efforts to establish the morality of adolescents through adolescent jam'iyah shalawat activities namely the existence of facilities that can support the activities, and most importantly the motivation or interest possessed by adolescents so that in the process of moral formation takes place and makes him moved to follow the activity. Meanwhile, the inhibiting factor is the decline in motivation in participating in activities and alsoenvironmental factors due to unfavorable interactions